The preservation of good cryptographic properties of mds matrix under direct exponentTransformation / Tran Thi Luong, Nguyen Ngoc Cuong, Luong The Dung - Tran Thi Luong
In this paper, some new results on the preservation of many good cryptographicproperties of MDS matrices under direct exponent transformation are presented